Fluorescence imprint alignment using additive-type inclination moiré fringes. (9th March 2020) - Yoshida, Takuma; Ito, Shunya; Ochiai, Kento; Nakamura, Takahiro; Nakagawa, Masaru
Abstract: It was studied whether additive-type fluorescence inclination moiré fringes were observed during imprint alignment by fluorescence microscopy using a pair of two periodical concave-line patterns with a long and short pitch of p 1 and p 2 prepared on silica mold and silicon substrate surfaces without any optically functional layer. A fluorescent liquid was sandwiched between the surfaces to fill into the concave lines and excited by exposure to visible light of 530–538 nm. In the detection wavelength range of 570–700 nm, additive-type fluorescence inclination moiré fringes generated from the place where bright concave lines with p 1 on the substrate were overlaid with bright concave lines with p 2 on the mold. The relationship of the mold-substrate angle deviation ( θ ) with the angle deviation ( ψ ) of an additive-type inclination moiré fringe was equal to the correlation of θ with the angle deviation ( φ ) of a multiplicative-type inclination moiré fringe.